2022
DOI: 10.1126/sciadv.abm8563
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of replicating and nonreplicating vaccines against SARS-CoV-2

Abstract: Most gene-based severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines are nonreplicating vectors. They deliver the gene or messenger RNA to the cell to express the spike protein but do not replicate to amplify antigen production. This study tested the utility of replication in a vaccine by comparing replication-defective adenovirus (RD-Ad) and replicating single-cycle adenovirus (SC-Ad) vaccines that express the SARS-CoV-2 spike protein. SC-Ad produced 100 times more spike protein than RD-Ad an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…This phenomenon is similar to previous findings suggesting that replication-competent recombinant adenoviruses (RCA) do not replicate efficiently in ICR mice [ 50 ]. However, it has been reported that wild-type human adenoviruses can replicate efficiently in Syrian hamsters and non-human primates [ 51 ], suggesting that RCA may pose potential safety risk. Meanwhile, no body weight changes and clinical symptom were observed in mice immunized with Adv-RVDG.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is similar to previous findings suggesting that replication-competent recombinant adenoviruses (RCA) do not replicate efficiently in ICR mice [ 50 ]. However, it has been reported that wild-type human adenoviruses can replicate efficiently in Syrian hamsters and non-human primates [ 51 ], suggesting that RCA may pose potential safety risk. Meanwhile, no body weight changes and clinical symptom were observed in mice immunized with Adv-RVDG.…”
Section: Discussionmentioning
confidence: 99%
“…The American pharmaceutical company Tetherex and the Mayo Clinic developed a replicating adenoviral vector ( SC-Ad6-1 ) that encodes a full-length spike; this vaccine is administered intranasally, and it aims to induce mucosal immunity [ 173 ] (Table 3 ). The single-cycle adenovirus replicates its genome (including the encoded spike transgene) 10,000 times but does not produce infectious virions.…”
Section: Pan-coronavirus Vaccine Approachesmentioning
confidence: 99%
“…The single-cycle adenovirus replicates its genome (including the encoded spike transgene) 10,000 times but does not produce infectious virions. SC-Ad6-1 was shown to produce 100-fold more spike protein and provided better protection in hamsters than a replication-defective Ad [ 173 ]. SC-Ad6-1 has entered Phase-I testing in Australia.…”
Section: Pan-coronavirus Vaccine Approachesmentioning
confidence: 99%